The Effect of Channel Length on Phase Transition of Phase Change Memory - S. A.Aziz, M; H. M.Fauzi, F; Mohamad, Z; I. Alip, R (International Journal of Engineering and Technology, 2018)
The phase transition of germanium antimony tellurium (GST) and the temperature of GST were investigated using COMSOL Multiphysic 5.0 software. Silicon carbide was using as a heater layer in the separate heater structure of PCM. These simulations have a different channel of SiC. The temperature of GST and the phase transition of GST can be obtained from the simulation. From the simulation, the 300 nm channel of SiC can change the GST from amorphous to crystalline state at 0.7V with 100 ns pulse width. The 800 nm channel of SiC can change the GST from amorphous to crystalline state at 1.1V with 100 ns pulse width. Results demonstrated that the channel of SIC can affecting the temperature of GST and the GST changes from amorphous state to crystalline state. As the channel of SiC decreased, the temperature of GST was increased and the GST was change to crystalline state quickly.Â Â